KAJIAN HUBUNGAN ARSITEKTUR MAJAPAHIT DENGAN ARSITEKTUR KERATON SURAKARTA DAN YOGYAKARTA DITINJAU DARI TATANAN RUANG, WUJUD, ORNAMENTASI, DAN TEKTONIKA - Stein, Ethan; Prajudi Herwindo, Rahadhian; Nirwan , Enrico (Jurnal Riset Arsitektur, 2025)
Abstract - The Hindu-Buddhist kingdoms emerged in Indonesia due to trade relations with other countries such as India, China, and the Middle East. One of the largest Hindu-Buddhist kingdoms with a vast territory covering the Nusantara region was the Majapahit Kingdom. Centered in East Java, this kingdom had a significant influence on the development of architecture in Indonesia, especially in Java, which was the center of governance at that time. One of the factors that led to the downfall of the Majapahit Kingdom was the phenomenon of Islamization. This led to the rapid growth of Islamic kingdoms on the island of Java. One prominent Islamic kingdom during that period was the Mataram Sultanate. The palaces established during the Mataram Sultanate included Keraton Kutagede, Kerta, Plered, Kartasura, and Surakarta Hadiningrat. In 1755, the Mataram Sultanate split due to power struggles, resulting in the establishment of the Surakarta Hadiningrat Sunanate and the Ngayogyakarta Hadiningrat Sultanate. As a result, the Ngayogyakarta Hadiningrat Palace was built in 1755. This research employs a descriptive method with a qualitative approach. The research data was obtained from literature studies, field observations, and interviews with experts. The aim of this study is to explore the relationship between Majapahit architecture and the palace buildings in Surakarta and Yogyakarta in terms of spatial order, form, ornamentation, and tectonics. Although the establishment of the Surakarta and Yogyakarta palaces occurred long after the Majapahit Kingdom, it is expected that Majapahit architecture had an influence on the architecture of the Surakarta and Yogyakarta palaces. However, it is possible that certain elements of Majapahit architecture have been lost over time due to cultural assimilation and adaptation to Islam. The analysis is conducted in a comparative manner and presented in the form of tables with accompanying explanations. From the comparative analysis, it is indeed evident that there are influence of Majapahit architecture on the palaces of Surakarta and Yogyakarta, which can be observed in terms of spatial order, form, ornamentation, and tectonics. The conclusion drawn from this research is that there is continuity and cultural acculturation between Hindu-Buddhist and Islamic cultures, which has influenced the design of the Surakarta and Yogyakarta palaces to this day. Keywords: Majapahit Architecture, Surakarta Palace, Yogyakarta Palace, Spatial Orders, Shapes, Ornamentation, Tectonics